New Technologies Smart, or Harm Work-Family Boundaries Management? Gender Differences in Conflict and Enrichment Using the JD-R Theory - Ghislieri, Chiara; Emanuel, Federica; Molino, Monica; Cortese, Claudio G.; Colombo, Lara (Frontiers in Psychology, 2017)
Background: The relationship between Technology-Assisted Supplemental Work and well-being outcomes is a recent issue in scientific literature. Whether the use of technology for work purpose in off-work time may have a positive or negative impact on work-family balance remains an open question and the role of gender in this relationship is poorly understood. Aim: According to the JD-R theory, this study aimed to investigate the relationship between off-work hours Technology Assisted Job Demand (off-TAJD) and both Work-Family Conflict (WFC) and Work-Family Enrichment (WFE). Moreover, it considered two general job demands, workload and emotional dissonance, and one job resource, supervisory coaching. Method: The hypotheses were tested with a convenience sample of 671 workers. Data were collected with a self-report questionnaire and analyzed with SPSS 23 and through multi-group structural equation model (Mplus 7). Results: The estimated structural equation model (Chi-square (510) = 1041.29; p < .01; CFI = .95; TLI = .95; RMSEA = .06 (.05, .06); SRMR = .05. M = 319 / F = 352) showed that off-TAJD was positively related to WFC in both subsamples; off-TAJD was positively related also to WFE only in the Male group. Workload was positively related to WFC in both Male and Female subsamples. Emotional dissonance was positively related to WFC in both subsamples and was negatively related to WFE. Supervisory coaching was strongly, positively related to WFE in both groups, and only in the Male subsample presented a low negative relationship with WFC. Conclusion: This study contributes to the literature on new challenges in work-life interface by analyzing the association between off-TAJD and Work-Family Conflict and Enrichment. Our findings suggest it is important to pay attention to gender differences in the study of the impact of supplemental work carried out during off-work hours using technology on the work-life interface. In fact, employee perception of Company demands of being available during off-work time, with the use of technology, may have different consequences for men and women, indicating potential differences in the centrality of the working role. Practical implications, at both cultural and organizational levels, should address the use of technology during leisure time.